Comprehensive analysis of the cuproptosis-related model to predict prognosis and indicate tumor immune infiltration in lung adenocarcinoma - Wu, Minle; Bao, Jie; Lei, Youfeng; Tao, Shuai; Lin, Qiurong; Chen, Liang; Jin, Yinpeng; Ding, Xiaohong; Yan, Yufeng; Han, Ping (Frontiers in Oncology, 2022)
Background: Cuproptosis is a novel form of programmed cell death termed as Cu-dependent cytotoxicity. However, the roles of cuproptosis-associated genes (CAGs) in lung adenocarcinoma (LUAD) have not been explored comprehensively. Methods: We obtained CAGs and utilized consensus molecular clustering by “Non-negative Matrix Factorization (NMF)” to stratify LUAD patients in TCGA (N=511), GSE13213 (N=117) and GSE31210 (N=226) cohorts. The ssGSEA and CIBERSORT algorithms were used to evaluate the relative infiltration levels of immune cell types in tumor microenvironment (TME). Risk score based on CAGs was calculated to predict patients’ survival outcomes. Results: We identified three cuproptosis-associated clusters with different clinicopathological characteristics. We found that cuproptosis-associated cluster with the worst survival rates exhibited the high enrichment of activated CD4/8+ T cells. In addition, we found cuproptosis-associated risk score could be used for patients’ prognosis prediction and provide new insights in immunotherapy of LUAD patients. Eventually, we constructed a nomogram integrated cuproptosis-associated risk score with clinicopathological factors to predict overall survival in LUAD patients, with 1-, 3- and 5- year area under curves (AUCs) being 0.771, 0.754 and 0.722, respectively, all of which were higher than those of TNM stage. Conclusions: In this study, we uncovered the biological function of CAGs in the TME, and its correlations with clinicopathological parameters and patients’ prognosis in LUAD. These finding could provide new angles for immunotherapy of LUAD patients.